Introduction to Basic Manufacturing. - Jawalkar, C. S. (Alpha Science International, 2016)
INTRODUCTION TO BASIC MANUFACTURING covers core basics and information about the major manufacturing processes. Practical examples, numericals and case studies have been included to elaborate the matter. The subject matter is presented in simple manner with practical approach so that the students need not search references and materials. As most of the interdisciplinary students face difficulties to refer to the existing (elaborated) texts and books in manufacturing since manufacturing is not their core area. This problem has been addressed clearly in the text and the subject has been made int.